Critical design in Japan : Material culture, luxury, and the avant-garde - Bartal, Ory (Studies in design and material culture., 2020)
This book tells the story of critical avant-garde design in Japan, which emerged during the 1960s and continues to inspire designers today. The practice communicates a form of visual and material protest drawing on the ideologies and critical theories of the 1960s and 1970s, notably feminism, body politics, the politics of identity, and ecological, anti-consumerist and anti-institutional critiques, as well as the concept of otherness. It also presents an encounter between two seemingly contradictory concepts: luxury and the avant-garde. The book challenges the definition of design as the production of unnecessary decorative and conceptual objects, and the characterisation of Japanese design in particular as beautiful, sublime or a product of 'Japanese culture'. In doing so it reveals the ways in which material and visual culture serve to voice protest and formulate a social critique.